Sosialisasi Perubahan Iklim Dalam Meningkatkan Produktivitas Tanaman Kopi Arabika Pada Kelompok Tani Tunas Jaya Aceh Tengah - Syahirman, Hakim; Salman, Salman; Irfannur, Irfannur; Izwar, Akmal; Muliari, Muliari (Aceh Journal of Community Engagement (AJCE), 2024)
The Tunas Jaya Farmers Group is an association of farmers in Damar Mulyo Village, Atu Lintang District, Central Aceh Regency. All of them are members of this farmer group as Arabica coffee farmers. The problem faced is the lack of information and knowledge regarding climate change and its impact on the productivity of Arabica coffee plants which can cause failure of coffee flowering, pest explosions and increased intensity of disease attacks which have an impact on coffee harvests. The aim of this activity is to provide knowledge and information to groups of farmers regarding the matters above, in order to increase coffee productivity. With a better understanding and knowledge of this matter, farmers are expected to be able to take appropriate steps to anticipate and adapt their cultivation techniques, so that it is hoped that Arabica coffee crop production can increase significantly. Socialization using lecture and discussion methods. Evaluation of activities consists of filling out pre-test and post-test questionnaires with 3 indicator components. The results showed an increase in participants' knowledge and understanding of the 3 indicator components given after the post-test evaluation.